STRATEGI RELOKASI PEDAGANG KAKI LIMA (PKL) DI TAMAN SULIKAN KABUPATEN LUWU UTARA - Nurlela Nurlela; Mappamiring Mappamiring; Muhammad Tahir (Kolaborasi : Jurnal Administrasi Publik, 2018)
This research aimed to explain how far the goverment’s strategy for the relocation of Pedagang Kaki Lima in Sulikan’s garden North Luwu Regency and made it to be the icon of Masamba City of North Luwu Regency. Sulikan’s garden had the strategic location for Pedagang Kaki Lima to sell their trades. The goverment relocated PKL because they were bothering and preventing, therefore PKL moved from Sulikan’s garden to the Market of Masamba which its location were far from Sulikan’sgarden. The source of this data were a primary data that was collected by an interview and direct observation of the informant, a secondary data were a documents or written and unwritten reports. Techniques data analysis applied in this research are an interview, observation, and documention. The data validity techniques used were triangulation of time, triangulation of data sources, and triangulation of theory. The result of the research showed that the goverment’s strategy for relocation and regualtion of PKL used five indicators 1) mission framing 2) objective and strategy 3) funtion systems and, 4) culture groups. 1) approval alocation 2) modals allocation and 3) facilities and infrastructures allocation. Keywords: strategy to relocate Pedagang Kaki Lima